Activity and topographic changes in the somatosensory system in embouchure dystonia. Issue 11 (7th June 2016) - Mantel, Tobias; Dresel, Christian; Altenmüller, Eckart; Zimmer, Claus; Noe, Jonas; Haslinger, Bernhard
ABSTRACT: Background: Embouchure dystonia is a highly disabling focal task‐specific dystonia affecting professional brass players. Objective: This study was designed to analyze activity changes along with topographic representations in primary and nonprimary centers for somatosensory processing in patients with embouchure dystonia. Methods: We used event‐related functional magnetic resonance imaging with automized tactile stimulation of dystonic (upper lip) and nondystonic (forehead and dorsal hand) body regions in 15 professional brass players with and without embouchure dystonia. Statistical analyses included whole‐brain between‐group comparisons of stimulation‐induced activation and region‐of‐interest‐based single patient analyses of topographic activation characteristics. Results: Affected musicians revealed increased stimulation‐induced activity in contralateral primary and bilateral secondary somatosensory representations of dystonic and nondystonic body regions as well as in the cerebellum ipsilateral to the left dystonic upper lip. Changes of somatotopic organization with altered intracortical distances and between‐group differences of the centers of representations were found in the right primary and the bilateral secondary somatosensory cortex and in the left cerebellum. Positional variability of dystonic and nondystonic body regions was reduced with an emphasis on face representations. Conclusions: The present findings are supportive of the concept of an abnormal processing of somatosensory information in embouchure dystonia affecting multiple domains. The underlying neurophysiological mechanisms (eg, changes in inhibition, maladaptive plasticity, changes in baseline activity) remain unclear. The involvement of nondystonic body areas can be viewed in the context of possible compensation or an endophenotypic predisposition. © 2016 International Parkinson and Movement Disorder Society